Pengaruh Korean Wave Dan Brand Ambassador Terhadap Minat Beli Konsumen Pada Platform E-Commerce Shopee Di Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Currently, internet technology is developing rapidly, increasing people's ability to access technology. The development of the Internet, Digital Technology and Communication also affects people's habits and lifestyles that are currently shifting from offline shopping to online shopping. Simple online shopping certainly affects consumer interest. Finding out how effective the Korean wave and brand ambassadors are in attracting customers is the aim of this study.  Since the study's participants were from Denpasar City and had never negotiated an e-commerce event, it was necessary to identify potential motivators for his initial purchase.  110 people made up the study's sample.  Likert scales for literature studies, interviews, questionnaires with five-choice answers, and observation techniques were all used in the data collection process.  Multiple linear regression analysis was employed for conventional acceptability and hypothesis testing following an assessment of the instrument's validity and reliabilityAccording to the survey's findings, brand ambassadors and the South Korean wave affected 57.4% of purchases.  Buy interest can occasionally be positively and significantly impacted by the Korean wave, and brand ambassadors can also positively and significantly influence buy interest.    Additionally, brand ambassadors and the South Korean wave significantly and favorably influence consumer purchasing. Based on these findings, businesses are encouraged to maintain and develop marketing strategies using the Korean wave and brand ambassadors by presenting more innovative and relevant advertising content to increase consumer interest.